Students' motivation to study Chinese recreational gymnastics classes wushu - O.V. Maksimuk; E.P. Vrublevskiy; Wang Lin (Physical Education of Students, 2014)
Purpose: to identify students' motivation to improving gymnastics lessons Chinese Wushu. Material : this survey was attended by 30 students from different countries enrolled in a language course at the Shanghai University of Sport. The methodology SAN (health, activity and mood). Results : the positive changes identified psycho-emotional state students. There is an increase students' motivation to sports activity. Students observed increase differentiated assessment of health (from 3.7 to 6.7 points), activity (from 3.9 points to 6.5 points) and mood (from 4.0 points to 6.9 points). 97 % of students were in favor of the use of functional music lessons on differentiated specialized Wushu. Conclusions : presented the program and practical advice on the organization and conduct physical education classes with students using the means of improving gymnastics Chinese Wushu.